Pemberdayaan Masyarakat Pesisir Kecamatan Sungai Sembilan Melalui Program Technofisheries Park Melalui Olahan Sirup Buah Mangrove - Sumartini (KREASI : Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2023)
Technofisheriespark is an integrated area (specially designed/planned, developed & managed) consisting of one or more IPTEKIN activity centers. The introduction and socialization activities were carried out in an effort to develop coastal communities and fishermen in the Geniot River area, Sungai Sembilan with the aim of providing mentoring and counseling programs regarding the potential of mangroves as raw materials for making syrup. This activity is carried out through the method of Design and socialization, operational assistance, and application of technology. At the beginning of the observation, it was seen that the entrepreneurs were interested in this training work program. Entrepreneurs looked enthusiastic until the end of the finalization of the training activities. This activity is expected to increase the income level of entrepreneurs in the Sungai Geniot community, foster creativity in making packaging and labels as well as product marketing, and the entrepreneurial skills of residents of Sungai Geniot Village, Sungai Sembilan District, Dumai City.